PERANAN PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) DALAM MENGHAPUSKAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DI KOTA BUKITTINGGI - Rafikah Rafikah (Islam Realitas: Journal of Islamic and Social Studies, 2015)
Violence in the house-hold (domestic violence) becomes an important issue in recent decades. According to the World Health Organization (WHO) between 40 to 70 percent of women in the world die for the violence in the household. In Indonesia, over the years the number of victims of domestic violence is increasing, so that led to the nativity of Law No. 23, 2004. By the law, there will be the power of law to govern the domestic violence cases in Indonesia, as well as an effort to overcome the problem of domestic violence in Indonesia. In order to provide the services for victims of violence at the Women and Child Protection, the Ministry of Women's Empowerment and Child Protection (State Ministry of PP & PA) formed the Integrated Service Center for Women's Empowerment and Child (P2TP2A), special for Bukittinggi. Women's Empowerment and Child Protection (P2TP2A) Bukittinggi is an integrated activity center that provides services for women and children victims of violence in Bukittinggi which includes information services, psychological and legal consultation, assistance and advocacy as well as medical services. Kekerasan Dalam Rumah Tangga (KDRT) menjadi isu penting dalam beberapa dekade terakhir ini. Menurut laporan World Health Organization (WHO) antara 40 hingga 70 persen perempuan di dunia meninggal akibat kekerasan yang terjadi dalam rumah tangga. Di Indonesia, dari tahun ke tahun jumlah korban KDRT selalu meningkat, sehingga mendorong lahirnya Undang-Undang No. 23 tahun 2004. Dengan Undang-undang tersebut, ada kekuatan hukum yang mengatur masalah kasus KDRT di Indonesia, sekaligus sebagai salah satu upaya untuk mengatasi permasalahan KDRT di Indonesia.  Secara spesifik, untuk memberikan pelayanan bagi korban kekerasan pada Perempuan dan Perlindungan Anak, Kementerian Negara Pemberdayaan Perempuan dan Perlindungan Anak (Kemeneg PP &PA) membentuk Pusat pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A). khusus Kota Bukittinggi. Pemberdayaan Perempuan dan Perlindungan Anak (P2TP2A) kota Bukittinggi adalah pusat kegiatan terpadu yang menyediakan pelayanan bagi perempuan dan anak korban kekerasan di Bukittinggi yang meliputi pelayanan informasi, konsultasi psikologis dan hukum, pendampingan dan advokasi serta pelayanan medis